Factors Influencing Indonesian Skincare Purchase Decision Using Korean Brand Ambassador with Purchase Intention as Intervening Variable - Syaharni, Dian Sabrina; Kesumahati, Erilia (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2023)
Skincare is one of the most important human needs at this time around the world, including in Indonesia. Attention to skin health to avoid skin problems has a very big impact. Various ways are used by companies to attract consumers to buy their products. This study aims to analyze the factors that influence purchase decisions. The research method uses a quantitative method by distributing questionnaires to people who use skincare in Batam City. The total number of respondents obtained was 440. The method of data analysis used Smart PLS version 3. The results of the research hypothesis directly that brand ambassador, brand image, promotion, brand loyalty, and purchase intention have a significant positive effect on purchase decision, while product quality does not significant positive effect on purchase decision. The result of the indirect hypothesis is that brand ambassador, product quality, and promotion have a significant positive effect on purchase decisions through intervening purchase intention, while brand image does not significant positive effect on purchase decisions through intervening purchase intention. It is hoped that this research will cover a wider range of research areas and can be used as a reference for other studies.